Chronic respiratory failure: an unusual cause and treatment. Issue 9 (1st September 2002) - Smyth, A; Riley, M
Abstract : Hypoventilation secondary to brainstem stroke resulting in chronic respiratory failure is extremely uncommon. This case documents the treatment of chronic type II respiratory failure secondary to central hypoventilation with medroxyprogesterone, a new treatment option.